2012
DOI: 10.1007/s12094-012-0787-1
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal cancer survival in Zaragoza (Spain): a population-based study

Abstract: The data suggest there were no significant changes in laryngeal cancer survival in the province of Zaragoza in the period 1978-2002 and that the tumours located in the glottis presented a better prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…Our results demonstrating no change in overall survival are in keeping with population-based studies from Australia, the Netherlands, Spain, and the United States (using data from the Surveillance, Epidemiology and End Results database) in patients with a new diagnosis of laryngeal carcinoma (Table viii) [35][36][37][38][39] . Using the U.S. National Cancer Database, both Hoffman et al 17 and Chen et al 15 found a decline in the survival of patients newly diagnosed with laryngeal cancer during the periods 1985-1996 and 1985-2007 respectively.…”
Section: Comparison With Other Studiessupporting
confidence: 82%
“…Our results demonstrating no change in overall survival are in keeping with population-based studies from Australia, the Netherlands, Spain, and the United States (using data from the Surveillance, Epidemiology and End Results database) in patients with a new diagnosis of laryngeal carcinoma (Table viii) [35][36][37][38][39] . Using the U.S. National Cancer Database, both Hoffman et al 17 and Chen et al 15 found a decline in the survival of patients newly diagnosed with laryngeal cancer during the periods 1985-1996 and 1985-2007 respectively.…”
Section: Comparison With Other Studiessupporting
confidence: 82%
“…In a population-based study in Zaragoza, Spain, a better survival rate was reported in patients with laryngeal SCC who were younger than 40 years compared to older patients. 10 Among patients with late-stage disease in our cohort, all were treated according to the same protocol as recommended by the National Comprehensive Cancer Network guidelines. Nevertheless, younger patients had a higher recurrence rate, and all recurred within 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the LSCC treatment strategies that have been developed in the past two decades, 32 , 33 , 34 satisfactory therapeutic outcomes and survival rates of patients with LSCC have not improved significantly. 35 Drug resistance and recurrence of malignancy are responsible for the uncertain therapeutic effects.…”
Section: Discussionmentioning
confidence: 99%